PENGEMBANGAN E-LEARNING BERBASIS MOODLE DENGAN MEDIA PEMBELAJARAN WHITEBOARD ANIMATION PADA MATA PELAJARAN RANGKAIAN ELEKTRONIKA DI SMKN 2 SUNGAI PENUH - Destra Amni (Indonesian Journal of Basic Education, 2020)
This research is motivated by the results of observations at SMK Negeri 2 Sungai Penuh, that there are problems namely limited time, effective weeks of students who are cut short of PSG time, very much and difficult material as well as the lack of learning media used. The steps used in this research are the research and development of R&D (research and development) with research procedures that have been modified at the mass production step replaced with analysis and reporting, the research steps include: (1) potential and problems, (2 ) data collection, (3) product design, (4) product validation, (5) product revisions, (6) limited product trials, (7) product revisions, (8) usage trials, (9) product revisions, ( 10) analysis and reporting. The subject of the trial was students of class XI TEI 1 at SMK Negeri 2 Sungai Penuh. The product trial design used was a before-after experiment. The feasibility of e-learning learning with Whiteboard Animation media in terms of validity and obtained the average value of the entire validation rating of 95.96% with a very valid category. The feasibility of learning media in terms of the effectiveness of obtaining the following results: (1) the learning outcomes of knowledge get the value of t count = 25.334> table = 2.457 with a significance level of 0.01. It can be concluded that the average posttest learning outcomes of students are better than the average pretest learning outcomes of students; (2) the results of learning skills get the value of t count = 11.192> t table = 1.80 with a significance level of 0.05. Then concluded that the average student learning outcomes are greater or equal to KKM; (3) the results of the observational assessment assessment sheet obtained an average rating of all aspects of 84.2%. The feasibility of e-learning learning in terms of practical aspects of filling out the questionnaire responses as many as 33 students get an average of 83.63% and are categorized very practical. From the explanation above, it can be concluded that the e-learning learning that was developed can be declared feasible in terms of validity, effectiveness and practicality.